2021
DOI: 10.1051/e3sconf/202131209001
|View full text |Cite
|
Sign up to set email alerts
|

Demand response strategies in residential buildings clusters to limit HVAC peak demand

Abstract: Due to the increasing spread of residential heating systems electrically powered, buildings show a great potential in producing demand side management strategies addressing their thermal loads. Indeed, exploiting the intrinsic characteristics of the heating/cooling systems (i.e. the thermal inertia level), buildings could represent an interesting solution to reduce the electricity peak demand and to optimize the balance between demand and supply. The objective of this paper is to analyse the potential benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some studies focus on demand response actions instead of a direct reduction on the power, such as [16] in which a hierarchical MPC is used for load shifting in a building, and [17] to perform DR actions at a building taking advantage of installed PV. However, less attention has been paid to DR oriented to a cluster of buildings, such as Energy Communities (EC), as [18] states. A few studies focusing on applying DR actions in an aggregated way can be found, such as [19] and [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies focus on demand response actions instead of a direct reduction on the power, such as [16] in which a hierarchical MPC is used for load shifting in a building, and [17] to perform DR actions at a building taking advantage of installed PV. However, less attention has been paid to DR oriented to a cluster of buildings, such as Energy Communities (EC), as [18] states. A few studies focusing on applying DR actions in an aggregated way can be found, such as [19] and [20].…”
Section: Introductionmentioning
confidence: 99%